Ushering children away from a “light grey world”: Dr. Daniel Hill III and his pursuit of a respectable Black Canadian community - McNeil, Daniel (Ontario History, 2007)
This paper is about Dr. Daniel Hill III, the first director of the Ontario Human Rights Agency. Paying particular attention to Dr Hill’s work with the Committee for the Adoption of Coloured Youngsters and the Ontario Black History Society, I argue that he fashioned himself as “Negro race man”, a masculinist term assigned to people who sought to lead a Black community in North America and lay to rest the infantilised and feminized image of the “tragic mulatto” trapped in a “light grey world”.